2018
DOI: 10.1016/j.adolescence.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Maternal support and deviance among rural adolescents: The mediating role of self‐esteem

Abstract: Introduction: Supportive mothering buffers against adolescent deviance, but the precise mechanisms underlying this relationship are poorly understood. The current investigation tested the extent to which self-esteem mediated the maternal support-deviance link and whether it varied by adolescent age and sex.Methods: Data were collected from 911 middle and high school students in the rural South (53.6% female, Mage = 14.70 years). Main model tests were completed in SEM.Results: Results indicated that maternal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 62 publications
0
7
0
1
Order By: Relevance
“…The third hypothesis was also confirmed, showing a negative correlation between all dimensions of self-esteem and an increased risk for ED, and a positive correlation between dimensions of self-esteem and FF. While on the one hand parenting is associated with self-esteem and satisfaction, on the other hand, parental styles may also be related to abnormal attitudes (Liu et al, 2018). Researchers point to the negative traits of a family system (overprotectiveness, difficulties with resolving disagreements and problematic situations, distance between family members or an atmosphere of tension or misunderstanding) as associated with EDs (Namysłowska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The third hypothesis was also confirmed, showing a negative correlation between all dimensions of self-esteem and an increased risk for ED, and a positive correlation between dimensions of self-esteem and FF. While on the one hand parenting is associated with self-esteem and satisfaction, on the other hand, parental styles may also be related to abnormal attitudes (Liu et al, 2018). Researchers point to the negative traits of a family system (overprotectiveness, difficulties with resolving disagreements and problematic situations, distance between family members or an atmosphere of tension or misunderstanding) as associated with EDs (Namysłowska et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have supported the mediating role of OBSE between employees’ cognition or work environment and their attitudes and behaviors. These connections include workplace ostracism and organizational citizenship behavior ( Li et al, 2021 ), maternal support and deviance ( Liu et al, 2018 ), abusive supervision and workplace deviance ( Vogel et al, 2015 ), etc. In the process of interacting with supervisors and colleagues, employees with IAS have different experiences in the organization due to differences in information processing methods and self-regulation strategies.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For instance, Frazer and Fite [19] found that parents' involvement in their children's lives was negatively related to depression symptoms and may buffer the impact of adverse experiences on depression. Supportive parenting is positively related to self-esteem [49] and cognitive and emotional self-control [7]. For example, when parents and teenagers engage in supporting interactions, teenagers learn their parents' cognitive control and problem-solving skills through observation and modeling [7,50].…”
Section: Supportive Parenting As a Moderatormentioning
confidence: 99%